2007
DOI: 10.1038/sj.bjc.6603711
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment parenthood in Hodgkin's lymphoma survivors

Abstract: Attempted and achieved post-treatment parenthood, with or without use of assisted reproduction techniques (ARTs), was assessed in Hodgkin's lymphoma survivors treated from 1971 -1998, aged below 50 (females) or 65 (males) at diagnosis, aged 18 to 75 at survey. Four treatment groups were constructed: radiotherapy only, low -, medium -and high gonadotoxic chemotherapy (with or without radiotherapy in the three chemotherapy groups). Using Kaplan -Meier estimates, log-rank tests and Cox regression analyses, factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 29 publications
(44 reference statements)
2
46
1
4
Order By: Relevance
“…The high success rate of maternity in our survey emerged among women who had tried to become mothers. The result is in concordance with a similar study in adults [28]. If all surveyed women were considered, the comparable rate is expected to be more in agreement with published figures [29], but still higher in females than in males (63% vs. 24%, P ¼ 0.04), this indicating higher gonadotoxicity in men than in women receiving the same treatments.…”
Section: Discussionsupporting
confidence: 81%
“…The high success rate of maternity in our survey emerged among women who had tried to become mothers. The result is in concordance with a similar study in adults [28]. If all surveyed women were considered, the comparable rate is expected to be more in agreement with published figures [29], but still higher in females than in males (63% vs. 24%, P ¼ 0.04), this indicating higher gonadotoxicity in men than in women receiving the same treatments.…”
Section: Discussionsupporting
confidence: 81%
“…We confirm the results from our previous study in HLSs, where we observed exocrine gonadal damage related to the type, cumulative dose and intensity of chemotherapy, assessed by post-treatment paternity (Kiserud et al, 2007). This study shows for the first time that the same categorization of chemotherapy in low, medium and highly gonadotoxic treatment can be useful also when exploring endocrine hypogonadism.…”
Section: Discussionsupporting
confidence: 80%
“…Treatment strategies of HL and NHL at the NRH for the period 1980 -2002 have been described earlier (Hagemeister et al, 1987;Merk et al, 1991;Evensen et al, 1994;Abrahamsen et al, 1996;Holte et al, 1996;Hollender et al, 2000;Aurlien et al, 2001;Seidemann et al, 2001;Sweetenham et al, 2001;Blystad et al, 2001aBlystad et al, , 2001bSmeland et al, 2004;Kiserud et al, 2007).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…По данным C. E. Kiserud с соавт., 2007, лишь около 20 % женщин, получивших лечение по поводу ЛХ, рожают впоследствии детей [39]. Помимо естественных причин (возраст, нали-чие детей до лечения ЛХ), существенную роль в этом играет как утрата фертильности вслед-ствие лечения ЛХ, так и ряд социальных и пси- Как показано ранее, большинство случаев прогрессирования и рецидивов ЛХ после тера-пии первой линии развивается в первые 2 года по завершении лечения [1,12].…”
Section: Discussionunclassified